PREFERENSI KONSUMEN TERHADAP PEMBLIAN CABAI RAWIT DI PASAR TRADISIONAL BADUNG KECAMATAN DENPASAR BARAT KOTA DENPASAR - Crisdayanti Manggut; Putu Fajar Kartika Lestari; Luh Putu Kirana Pratiwi; Ni Putu Sukanteri (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
The research objective with the title "Consumer Preferences Against the Purchase of Cayenne Pepper at the Badung Traditional Market, West Denpasar District, Denpasar City". Respondents in this study were determined as many as 30 consumers with the purposive method. The results of the research on consumer perceptions of the purchase of cayenne pepper based on the five variables, namely attitude, selection, organization, physical characteristics, interpretation and the one who gets the highest percentage is the attitude variable. with a score of 660, an average of 22.01 and a percentage of 85.00% and is in the very good category with 25 respondents. And based on the explanation of the five variables of consumer perception are in the very good category with a percentage of 80.00% and the number of respondents is 24 people. The level of consumer preference for the purchase is based on the five variables, namely the physical quality of the product, safety and convenience of the location, price suitability, personal factors, psychological factors and the one who gets the highest percentage is the physical quality of the product and the suitability of the price with a total score of 750, on average. the average is 25 and the percentage is 100% and is in the very good category with 30 respondents. And based on the explanation of the five consumer preference variables are in the very good category with a percentage of 95.00% and the number of respondents is 28 people